2024
DOI: 10.1021/acs.estlett.4c00342
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 6PPD-quinone In Vitro Using RTL-W1 Cell Line

Phillip J. Ankley,
Francisco C. da Silva,
David Montgomery
et al.

Abstract: Urban stormwater runoff contains the tire-derived transformation product N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine-quinone (6PPD-quinone), which poses significant environmental risks due to its high toxicity toward certain salmonids. 6PPD-quinone biotransformation has been investigated to explain some of the stark interspecies differences in sensitivity across different fishes; however, the primary mechanisms of 6PPDquinone biotransformation remain unclear. This work aimed to explore the toxicokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The two monohydroxylated TPs ( m/z = 315.17) included an alkyl sidechain hydroxylation (TP-OH1, RT = 13.45) and a phenyl ring hydroxylation (TP-OH2, RT = 14.56), both of which have been previously described. 11 TP-OH1 was only detected in the more sensitive fish species for the 2-2.5 µg/L exposure bin (Figure 1D), with BRT only having TP-OH2 present. The dihydroxylated TP ( m/z = 331.17) showed identical fragmentation patterns for all species, indicating a phenyl ring hydroxylation and alkyl sidechain hydroxylation, and was found to be greatest in RBT (averaged sum; 3.30x10 4 arbitrary units, au), followed by LKT (5.74 × 10 2 au) and BRT (4.31 × 10 2 au) (Figure 1D).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The two monohydroxylated TPs ( m/z = 315.17) included an alkyl sidechain hydroxylation (TP-OH1, RT = 13.45) and a phenyl ring hydroxylation (TP-OH2, RT = 14.56), both of which have been previously described. 11 TP-OH1 was only detected in the more sensitive fish species for the 2-2.5 µg/L exposure bin (Figure 1D), with BRT only having TP-OH2 present. The dihydroxylated TP ( m/z = 331.17) showed identical fragmentation patterns for all species, indicating a phenyl ring hydroxylation and alkyl sidechain hydroxylation, and was found to be greatest in RBT (averaged sum; 3.30x10 4 arbitrary units, au), followed by LKT (5.74 × 10 2 au) and BRT (4.31 × 10 2 au) (Figure 1D).…”
Section: Resultsmentioning
confidence: 96%
“…This provides additional evidence that the preferred phenyl ring monohydroxylation occurs at the para position due to increased availability for CYP biotransformation and decreased steric hindrance. 11 Phase I to phase II normalized relative abundance ratio values indicated that RBT had the lowest capacity to conjugate hydroxylated TPs (Figure 1C), followed by LKT. BRT had the greatest ability to biotransform hydroxylated TPs further through phase II conjugation, which could have important implications for the differences in the reported species-specific sensitivities to 6PPD-Q.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations